Erdheim-Chester disease with epiphyseal and systemic disease. Issue 5 (May 1993) - Athanasou, N A; Barbatis, C
Abstract : A case of Erdheim-Chester disease which affected the epiphysis and showed evidence of systemic disease is presented. Clinical and histopathological similarities with other forms of disseminated Langerhans' cell histiocytosis are noted, particularly reaction of infiltrating histiocytes for S100 and HLA-DR.